Safer school with near-UVA technology: novel applications for Environmental Hygiene: Roberta Bosco. (25th October 2022) - Bosco, R; Amodeo, D; De Palma, I; Cevenini, G; Messina, G
Abstract: Background: Schools are crowded places where outbreaks can occur. Systems capable of disinfecting air and surfaces could reduce the risk of transmission of infectious diseases. Aim: to evaluate the effectiveness of a near-UVA (nUVA) LED ceiling lamp in improving environmental hygiene. Methods: This cross-sectional study was conducted for 2 weeks between November and December 2020 in a kindergarten in Siena, Italy. Four ceiling lamps with LED wavelength of 405 nm were mounted on the room ceiling. The distance of the lamps from the floor was 2.70 m and 2.0 m from the desks. We preliminary selected 12 points in different sites of the room by measuring their irradiance values. We randomly sampled between 8 and 12 pairs of Petri Dishes (PD) daily during the study, incubated at 22 and 36C°, at different irradiation times: 8, 12 or 36 hours. Paired controls were used before using the lamps (at time T0), which were automatically switched ON overnight and compared with treatment (at time T1). Air sampling was also performed at T0 and T1. Statistical analysis was performed with Stata 14. Significance was set at 95% (p < 0.05). Results: 520 PDs were used in the study: 130 PDs at T0 matched at T1 incubated at 36 °C and as many at 22 °C. The mean level of contamination at T0 was respectively 249 CFU (95 % CI 193.1 - 305.0) at 36 °C and 535.2 CFU (374.3 - 696.1) at 22 °C. The reduction was significant (p < 0.05) at T1: we had 87.4 CFU (56.3 - 118.6), equal to 65%, at 36C° and 149.6 CFU (83.7 - 215.4), equal to 72%, at 22C°. Different values were recorded stratifying for dose (irradiance per exposition time). A significant mean percentage reduction of air contamination was 95.3% (98.4 - 92.3). Conclusions: The system was able to improve the environmental hygiene of the kindergarten. The advantage of using this technology in the presence of people is very important in the context of controlling environmental contamination. Key messages:  Near-UVA are efficient in reducing the contamination level significantly in a real-life context, on the surfaces and of the air.  Crowded places favour germ outbreaks. Hygiene control is essential to reduce the risk of transmission of infectious diseases.